The Implementation of Project Based Learning in Translation/Interpreting I Course - Adiwijaya, Pande Agus (Journal of Psychology and Instructions, 2017)
The change of paradigm of university education level in Indonesia has demanded changes in its curriculum. More skill-based curriculum is demanded as the result of global competition. As the paradigm change, the teaching method is should be changed as well. Translation/Interpreting I course in English Education Department of STKIP Suar Bangli has been changed to be more skill-based course as before it was emphasized on theory only. This course was taught by using Project Based Learning approach in order to give more practices to the students rather than teaching theories. This approach was conducted in 1 semester consisting of 16 meetings. It was done in fifth semester students of English Education Department of STKIP Suar Bangli. It was qualitative descriptive study which aiming at describing how was the implementation of Problem Based Learning in this course. Some instruments were utilized such as documentation, observation sheet, questionnaire and evaluation rubric. The data were analysed quantitatively and qualitatively. Based on the finding it was found that the students were having probem in the beginning of this implementation but finally they realized that this approach is much more helping them in learning translation/interpreting I.Â